1987
DOI: 10.1093/bja/59.12.1497
|View full text |Cite
|
Sign up to set email alerts
|

Some Ventilatory Effects of Propofol as Sole Anaesthetic Agent

Abstract: Ventilatory effects of propofol, used as a sole agent for the induction and maintenance of general anaesthesia, were studied in 14 healthy unpremedicated patients. Subarachnoid anaesthesia was established before induction of general anaesthesia. Induction was with propofol 2.5 mg kg-1 given while the patients breathed 100% oxygen. We intended to start an infusion of propofol 100 micrograms kg-1 min-1; maintain it for at least 25 min; make a first set of quasi-steady-state observations; double the infusion; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
65
2
11

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(85 citation statements)
references
References 15 publications
7
65
2
11
Order By: Relevance
“…Although opioids are frequently used with propofol to improve LMA insertion conditions in clinical practice, 17 co-administration of both agents may increase the incidence and duration of apnea due to their synergistic effect on respiratory depression. 18,19 The incidence of apnea may reach 70% following the use of propofol 2.5 mgÁkg -1 alone and 83.3% following the use of propofol 2.5 mgÁkg -1 plus fentanyl 1 lgÁkg -1 . 20 Apnea is probably of little consequence when the airway is protected with the LMA.…”
mentioning
confidence: 99%
“…Although opioids are frequently used with propofol to improve LMA insertion conditions in clinical practice, 17 co-administration of both agents may increase the incidence and duration of apnea due to their synergistic effect on respiratory depression. 18,19 The incidence of apnea may reach 70% following the use of propofol 2.5 mgÁkg -1 alone and 83.3% following the use of propofol 2.5 mgÁkg -1 plus fentanyl 1 lgÁkg -1 . 20 Apnea is probably of little consequence when the airway is protected with the LMA.…”
mentioning
confidence: 99%
“…This combination aims to capitalise on the primarily hypnotic and analgesic properties of each drug, respectively. Propofol, at the recommended induction dose (2.0±2.5 mg.kg 21 ), can cause cardiovascular and respiratory depression [5,6]. The extent of hypotension, degree of bradycardia and the duration of apnoea are dose related but can be unpredictable even in fit young patients.…”
mentioning
confidence: 99%
“…Goodman et al found that the HCVR decreases to 58 % of its baseline after a 2.5 mg kg -1 bolus of propofol followed by an infusion of 100 mcg kg -1 min -1 [64]. Blouin et al [67] demonstrated that the slope of the CO 2 response curve decreases by 56 % after a 2.5 mg kg -1 bolus of propofol.…”
Section: Propofolmentioning
confidence: 99%
“…Two separate groups demonstrated that the decreased minute ventilation observed after a propofol bolus is more attributable to decreased tidal volume than to decreased respiratory rate [59,60]. After induction of anesthesia with propofol (2.0-2.5 mg kg -1 ) alone, periods of apnea more than 30 s occur in at least 60 % of patients [61][62][63][64]. These episodes may extend to 60 s or more in 33-50 % of patients receiving the same dose of propofol after pretreatment with an opioid [59,65,66].…”
Section: Propofolmentioning
confidence: 99%